Mutual events between Galilean satellites observed with SARA 0.9 m and 0.6 m telescopes during 2014–2015. Issue 4 (10th November 2018) - Zhang, X L; Han, X L; Arlot, J E
ABSTRACT: Observation of mutual events has been confirmed to be a most effective and accurate ground-based method for obtaining accurate astrometric data by fitting the flux variation of involved satellites during the events, which is very invaluable for improving the orbital models of the natural satellites. The mutual events between the Galilean satellites occur every six years. During the observational campaign of 2014–2015, 21 mutual events between Galilean satellites were observed with the SARA 0.9 m and 0.6 m telescopes. The model proposed by Assafin et al. and Zhang et al. for mutual occultation and Zhang et al. for mutual eclipse were used to fit the light curves, taking the Lommel–Seeliger scattering law and the solar limb darkening into account. In this paper, the astrometric results of the Galilean satellites from the mutual events we observed will be shown, such as the impact parameter and its corresponding mid-time, and the velocity of occulting/eclipsing satellite relative to the occulted/eclipsed one.